Analisis Pentingnya Penerapan Aksiologi dalam Kehidupan Sehari-Hari - Nurna, Nurna; Natasya A, Aurel; Rahmawati, Rahmawati; Dewi, Anita Candra (JURNAL EDUKASI NONFORMAL, 2025)
The purpose of this article is to understand, analyze or explain the importance of the application of axiology in everyday life. In this study, the method used is a qualitative descriptive method with reading and writing techniques that prioritize the description of data through words that contain thousands of meanings. Data were collected from articles and philosophy books. Axiology is important in everyday life because it determines how we act, make decisions, and interact with others. By having a good understanding of the values in axiology, we can live by the right principles, uphold honesty, justice, and morality. Axiology also helps us understand how these values can be applied in various contexts of life, from family, education, work, to society and the international world.